Uncertainty and justice experiences in the context of organizational change: a qualitative deductive study - Nordhall, Ola; Hörvallius, Julia; Nedelius, Mathilda; Knez, Igor (Frontiers in Organizational Psychology, 2025)
We investigated employees' experiences of uncertainty and procedural justice of organizational change by a theory-driven approach where the interview guide and analyses were based on theoretical, predetermined themes. The results showed mixed combinations of uncertainty and procedural justice experiences. Uncertainty experiences were combined with experiences of procedural justice and with a lack of procedural justice experiences of the organizational change. Participants who had experiences of uncertainty had no qualitatively different experiences of procedural justice compared to those who did not experience uncertainty. Theoretical implications and practical relevance of the results obtained in a context of an organizational change are discussed.